Animal Behaviour: Evolution and Mechanisms - Anthes, Nils; Bergmüller, Ralph; Blanckenhorn, Wolf; Brockmann, H. Jane; Fichtel, Claudia; Fromhage, Lutz; Frommen, Joachim; Goymann, Wolfgang; Heinze, Juergen; Hirschenhauser, Katharina; Hofer, Heribert; Kaiser, Sylvia; et al. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The study of animal behaviour is one of the fastest growing sub-disciplines in biology. The resulting diversity of conceptual approaches and methodological innovations makes it increasingly difficult for professionals and students to keep abreast of important new developments. This edited volume provides up-to-date reviews that facilitate orientation in key areas of animal behaviour, including communication, cognition, conflict, cooperation, sexual selection and behavioural variation. The contributions address evolutionary and proximate aspects of behaviour and also cover both invertebrates and vertebrates. Important concepts are dealt with in separate glossaries and key examples highlighted in separate text boxes. Richly illustrated with colour figures, this volume offers a well structured overview of all the main developments in current animal behaviour research. It is ideal for teaching upper-level courses, where it will be essential reading for advanced students familiar with basic concepts and ideas.